Assessing the impact of Ascariasis and Trichuriasis on weight gain using a porcine model. - Bradley Whitehead; Stig M Thamsborg; Matthew J Denwood; Peter Nejsum (Public Library of Science (PLoS), 2022)
Background Infections with Ascaris lumbricoides and Trichuris trichiura remain significant contributors to the global burden of neglected tropical diseases. Infection may in particular affect child development as they are more likely to be infected with T. trichiura and/or A. lumbricoides and to carry higher worm burdens than adults. Whilst the impact of heavy infections are clear, the effects of moderate infection intensities on the growth and development of children remain elusive. Field studies are confounded by a lack of knowledge of infection history, nutritional status, presence of co-infections and levels of exposure to infective eggs. Therefore, animal models are required. Given the physiological similarities between humans and pigs but also between the helminths that infect them; A. suum and T. suis, growing pigs provide an excellent model to investigate the direct effects of Ascaris spp. and Trichuris spp. on weight gain. Methods and results We employed a trickle infection protocol to mimic natural co-infection to assess the effect of infection intensity, determined by worm count (A. suum) or eggs per gram of faeces (A. suum and T. suis), on weight gain in a large pig population (n = 195) with variable genetic susceptibility. Pig body weights were assessed over 14 weeks. Using a post-hoc statistical approach, we found a negative association between weight gain and T. suis infection. For A. suum, this association was not significant after adjusting for other covariates in a multivariable analysis. Estimates from generalized linear mixed effects models indicated that a 1 kg increase in weight gain was associated with 4.4% (p = 0.00217) decrease in T. suis EPG and a 2.8% (p = 0.02297) or 2.2% (p = 0.0488) decrease in A. suum EPG or burden, respectively. Conclusions Overall this study has demonstrated a negative association between STH and weight gain in growing pigs but also that T. suis infection may be more detrimental that A. suum on growth.